Pembangunan Dan Keterbelakangan (Suatu Studi Kemiskinan Tentang Implikasi Kebijaksanaan Pembangunan Dan Strategi Survival Kaum Miskin Dalam Megatasi Kemiskinannya Du Wilayah Hinterland Kotamadya Batam) Development and Un - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
As a strategic area designed for a centre of growth in the region, Batam Municipality (mainly Batam Island as a core region) has been planned to be a modem "Island City" which has spesific functions as an industrial zone, trade centre, tourist destination, logistics warehouse and the transhipment base. To achieve those goals, the Central Government has determined various development policies. The politics of regional development of Batam tends to be critisized due to its "urban bias", creats no unleast less benefit to "the local people", adopted the big push strategy and has pushed economic growth with less developmental distribution effect, hypher (Pseudo) urbanization, rural breakdown and depopulation. The idea of Batam as an engine of growth for its surroundings (hinterland) is still far from the reality of development. The concentration of development in urban area and modem sector induced by MNCs (Multi National Cooperations) has neglected the majority of the rural poors who are living in the underdeveloped area. The tendencies of regional economic policies in macrocospic (regional) approach and quantitative data justification has strengthened the vicioes circles of poverty underdevelopment and inequalities in the rural area (fishermen subsistence economy). Although many of the rural poors has less access to the developmental opportunity,but they have their own survival strategies in alleviating the poverty phenomena. The survival strategies are (vertically or horizontally) social and interpersonal nettworks realationships, off-farms jobs (efforts diversification), urbanization and migration, adoption and adaptation of the culture of poverty.